2015
DOI: 10.5005/jp-journals-10005-1281
|View full text |Cite
|
Sign up to set email alerts
|

A Polarized Light Microscopic Study to Comparatively evaluate Four Remineralizing Agents on Enamel viz CPP-ACPF, ReminPro, SHY-NM and Colgate Strong Teeth

Abstract: Aim: To compare and evaluate the remineralizing potential of four commercially available products namely SHY-NM, GC Tooth Mousse Plus, ReminPro and Colgate strong teeth on demineralized human teeth.Materials and methods: The study included 50 extracted premolars having 3 × 3 mm window prepared on the middle third of the tooth, which was then subjected to demineralization for 48 hours at 37°C. Teeth were randomly selected and grouped into five study groups of 10 teeth in each. Each group was treated with respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 11 publications
3
26
0
1
Order By: Relevance
“…Evidence-based review and research studies on the calcium phosphate agent for prevention of tooth caries in children indicated that calcium and phosphate ion promote remineralization of early enamel caries,[37383940414243444546474849] which is in line with the results of this study; however, which type of calcium phosphate compound is the best remineralizing agent is still controversial. [4243444546474849]…”
Section: Discussionsupporting
confidence: 84%
“…Evidence-based review and research studies on the calcium phosphate agent for prevention of tooth caries in children indicated that calcium and phosphate ion promote remineralization of early enamel caries,[37383940414243444546474849] which is in line with the results of this study; however, which type of calcium phosphate compound is the best remineralizing agent is still controversial. [4243444546474849]…”
Section: Discussionsupporting
confidence: 84%
“…In all of the in vitro studies [28][29][30][31][32][33][34][35]38 described above in which human teeth were used; all researchers demonstrated Novamin as an effective remineralizing agent as in our study, but there were some differences found between the studies, such as novamin which was found more effective in some studies 34,35 or less effective in other studies than dentrifices including fluoride and CPP-ACP. Some studies found no statistical differences between dentrifices in remineralizing potential as in our study.…”
Section: Discussionmentioning
confidence: 85%
“…In another in-vitro study, when they compared the remineralizing potential of four commercially available products namely SHY-NM (Novamin), GC Tooth Mousse Plus (CPP-ACP and 900 ppm fluoride), ReminPro (hydroxyapatite 1450 ppm fluoride and Xylitol) and Colgate strong teeth (1000 ppm fluorid) on demineralized human teeth, SHY-NM had the most remineralizing potential followed by ReminPro, GC Tooth Mousse Plus and fluoridated toothpaste. 30 Mettu et al 31 reported that CPP-ACP increases enamel surface hardness. In a study, the CCP-ACP paste showed remineralizationinducing effect on artificially induced initial caries lesions.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with a study by Marchetti E et al, which demonstrated a continuous increase in mineral gain and the return of the microhardness values to near baseline level when a HA based cream was used after bleaching procedure 18 . In several studies this has been attributed to the filling of the irregular enamel of the bleached surface with hydroxyapatite (HA) crystals and the formation of fluorapatite (FA) due to the high fluoride content of 1450 ppm fluoride, which is 61% higher than other brands available [900 ppm in CPP-ACPF & 950 ppm in β-TCP] 19,20,21 .…”
Section: Methodsmentioning
confidence: 99%